TESTICULAR TORSION INDUCED BY EPIDIDYMO-ORCHITIS: A RARE CASE REPORT - Febriansyah, Nafis Audrey; Djatisoesanto, Wahjoe; Rizaldi, Fikri (Indonesian Journal of Urology, 2026)
Objective: We report a case of an episode of acute scrotum within 4 days. To our knowledge, this is a rare case of epididymo-orchitis predisposing to testicular torsion. This paper has been reported in line with the SCARE 2023 criteria. Case(s) Presentation: This case involves a 17-year-old male with worsening scrotal pain and swelling following minor trauma, accompanied by intermittent fever. Physical examination revealed left testicular enlargement and tenderness, with a negative Prehn’s test. Doppler ultrasound indicated decreased blood flow and a whirlpool sign, suggesting torsion. Discussion: Emergency scrotal exploration confirmed a 180-degree spermatic cord torsion with partial testicular necrosis, necessitating orchiectomy and orchidopexy. The patient had a smooth recovery. Conclusion: Testicular torsion requires prompt diagnosis and intervention for optimal outcomes. Keywords: Testicular torsion, epididymo-orchitis, case report.